High sensitivity low cost capacitive strain gage - Da Silva, Josivaldo Godoy [UNESP]; De Carvalho, Aparecido Augusto [UNESP]; Rodrigues, Rogério de Oliveira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2004)
This paper describes a high senstivity low cost capacitive strain gage sensor. The theory, design, and sensor construction details are presented. It consists of eight capacitive sensors connected in two full bridges. The capacitive strain gage sensor structure was designed in order to produce high sensitivity and low dependence with temperature. By using a simple signal conditioning circuit constituted by a differential amplifier, a band-pass filter, and a precision rectifier the device can measure forces with resolution of 0.009 N and precision of 98.7%. It is rugged, presents linear response, and good repeatability. It presents sensitivity of 8.7 V/N and fall time of 12 ms.
Keywords: Capacitive sensor; Capacitive strain gage; High sensitivity; Strain gage; Capacitive sensors; Capacitive strain gages; Mechanical systems; Bandpass filters; Costs; Differential amplifiers; Force measurement; Sensitivity analysis; Sensors; Signal processing; Thermal effects; Strain gages